2000
DOI: 10.1046/j.1365-2648.2000.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of safer sex communication among college students

Abstract: Correlates of safer sex communication among college students The purpose of this study was to examine factors that are thought to promote communication about safer sex and HIV among college students in the United States of America and to determine the extent to which communication about safer sex is important in the use of condoms. A better understanding of factors associated with safer sex communication can be helpful in developing HIV and STD prevention programmes for college students. Following approval fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 18 publications
5
37
2
1
Order By: Relevance
“…Regarding perceived norms, it predicted greater perceived peer sexual activity (i.e., peer descriptive norms) in one study (Leland and Barth 1993), more perceived social consequences of sex in one study (i.e., injunctive norms; Dittus et al 1999), greater parental disapproval of sex in one study (Jaccard et al 1998), and was unrelated to peer norms in one study (Ragsdale et al 2013). Finally, overall extent of parent-adolescent sexual communication was significantly related to greater safe-sex efficacy in three studies (DiIorio et al 2000;Mastro and Zimmer-Gembeck 2015;Shoop and Davidson 1994) and unassociated with efficacy to refuse unwanted sex in one study (Somers and Ali 2011).…”
Section: Overall Extent Of Parent-adolescent Sexual Communicationmentioning
confidence: 97%
See 2 more Smart Citations
“…Regarding perceived norms, it predicted greater perceived peer sexual activity (i.e., peer descriptive norms) in one study (Leland and Barth 1993), more perceived social consequences of sex in one study (i.e., injunctive norms; Dittus et al 1999), greater parental disapproval of sex in one study (Jaccard et al 1998), and was unrelated to peer norms in one study (Ragsdale et al 2013). Finally, overall extent of parent-adolescent sexual communication was significantly related to greater safe-sex efficacy in three studies (DiIorio et al 2000;Mastro and Zimmer-Gembeck 2015;Shoop and Davidson 1994) and unassociated with efficacy to refuse unwanted sex in one study (Somers and Ali 2011).…”
Section: Overall Extent Of Parent-adolescent Sexual Communicationmentioning
confidence: 97%
“…In three studies, path models and/or mediation analyses showed that parent-adolescent sexual communication was related to greater efficacy to use condoms and to communicate with a sexual partner about safe sex practices, which were then associated with greater safe sex behavior (e.g., fewer sexual partners, fewer instances of unprotected sex) (DiIorio et al 2000;Hutchinson et al 2003;Malcolm et al 2013). One study showed that parentadolescent sexual communication was not indirectly related to sexual intentions via self-efficacy to refuse unwanted sex (Beadnell et al 2007).…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gebhardt, Kuyper, and Greunsven (2003) reported that adolescents' attitudes toward condom use were associated with actual condom use during their sexual exposure. Additionally, Diiorio, Dudley, Lehr, and Soet (2000) reported that self-efficacy in condom use was a major factor affecting condom use among adolescents.…”
mentioning
confidence: 98%
“…In response to surveys conducted by the National Campaign to Prevent Teen Pregnancy, teens reported that their parents have more influence on their sexual decision-making than their friends, siblings, educators, or the media [6]. Recent studies suggest that parents may have more impact on adolescents' sexual behavior than do teen peers [7][8][9] and that parent-teen communication about sexual issues may have a protective effect that extends into the adolescents' college years [10,11]. Furthermore, to have the greatest impact on sexrelated behavior, parental communication with children about sexuality should take place sooner rather than later [12,13].…”
mentioning
confidence: 98%